LANGUE BAHASA INDONESIA UNTUK MENGEMBANGKAN KREATIVITAS MAHASISWA - Dheka Dwi Agustiningsih; Erik Rusmana (Jurnal Semantik, 2017)
This paper discussed Bahasa Indonesia as one of the general course in higher education. In the university, this subject includes in personality development. Therefore, the purpose of this subject is not limited to the ability to use the rules of language in communication. This paper aims to show that at the level of langue, Indonesian can be used to develop student creativity. The concept of this langue as proposed by Saussure. Within this concept, there are syntagmatic and associative relationships that can be used to develop student creativity through scientific papers. The method used in this research is descriptive qualitative. Based on the analysis that already conducted, found that through a search of constituents which have syntagmatic and associative relations in the form of words, phrases, and sentences, then we can found the new ideas and creativity can be developed and contained in the form of scientific papers.